A survey of the use of arterial catheters in anesthetized dogs and cats: 267 cases. Issue 1 (27th September 2016) - Trim, Cynthia M.; Hofmeister, Erik H.; Quandt, Jane E.; Shepard, Molly K.
Abstract: Objectives: To describe the clinical practice of insertion of arterial catheters in anesthetized dogs and cats, to document complications of arterial catheterization, and to determine risk factors associated with the complications. Design: Prospective clinical study and retrospective evaluation of medical records. Setting: University teaching hospital. Animals: Dogs ( n = 251) and 13 cats anesthetized for clinical procedures with arterial catheters inserted for blood pressure monitoring. Interventions: None. Measurements and Main Results: Details of the animal and catheter were collected at the time of anesthesia. On the following day, the catheter site was palpated and observed for abnormalities and the medical records of all animals were reviewed retrospectively for complications. Details of catheter placement were available for 216 catheters: 158 catheters in a dorsal pedal artery, 50 catheters in the median caudal (coccygeal) artery, 6 in the median artery, and 1 each in a cranial tibial and lingual artery. Blood pressure was obtained from 200 catheters, and 12 catheters failed before the end of anesthesia. Postoperative observational data obtained from 112 catheters described a palpable arterial pulse at 73 sites and no pulse at 21 sites. No risk factor for arterial occlusion was identified. No complications resulting from arterial catheterization were noted in the medical records. Conclusions: Arterial catheterization resulted in loss of a peripheral pulse postoperatively in 21/94 (22.3%) of animals examined, although no evidence of tissue ischemia was noted in the medical records of any of the patients in this study. These results suggest that insertion of a catheter in the dorsal pedal or coccygeal arteries was not associated with a high risk for complications. However, the course of arterial occlusion postoperatively warrants further investigation.